Breast lobular carcinoma in situ associated podocytopathy. Issue 3 (October 2020) - Muzib, Abdulrahman; Wanchoo, Rimda; Jhaveri, Kenar D
Paraneoplastic glomerular diseases are rare. While membranous nephropathy has been classically associated with solid malignancies, minimal change disease has been commonly described with hematologic malignancies. Other podocytopathies such as focal segmental glomerulosclerosis have not been classically associated with solid malignancy. In this case report, we present a case of a 52-year-old female with a diagnosis of focal segmental glomerulosclerosis associated with breast lobular carcinoma in situ. The focal segmental glomerulosclerosis diagnosis preceded the diagnosis of the breast cancer. While the proteinuria came into partial remission with conservative management, a dramatic resolution of focal segmental glomerulosclerosis was noted post-surgery and hormonal therapy for the breast cancer.